A three dimensional simulation of spray cooling and its evaporating liquid film generated on patterned surfaces. (October 2022) - Zeraatkardevin, Amirhooshang; Jowkar, Saeed; Morad, Mohammad Reza; Shen, Xing
Highlights: Spray cooling heat transfer of various surface structures are investigated numerically. 3D Euler-Lagrangian simulation is performed and wall-film model is used. Liquid film thickness and streamlines are computed in the vicinity of different fin geometries. Local film thickness increases in grooves. The film velocity magnitude depends on the fin blockage. Abstract: Liquid impingement cooling in the form of jet or spray is an appropriate method to remove heat from small surfaces progressively utilized in industry. In this study, numerical simulations are conducted to investigate the effect of surface structure on heat transfer characteristics. Five different three-dimensional structured surfaces are investigated using Euler-Lagrangian approach. The effect of surface structures is discussed on the liquid film thickness, the liquid film velocity, and the heat flux with its uniformity for a given spray and temperature characteristics. The results show that the convective heat transfer strongly depends on both liquid film thickness and velocity. While the liquid film thickness always grows in the grooved surfaces, its velocity depends on the form and direction of the fins. The averaged values of the film thickness and velocity magnitude are almost independent of the surface temperature. Among the investigated surfaces, the parallel and circular patterns showed the best and worst performance on heat transfer characteristics, respectively.